Perancangan Sistem Informasi Layanan Monitoring Hasil Perkebunan Kelapa Sawit Berbasis Website di PT. Adimulia Palmo Lestari (APL) - Sri Wahyuningsih; Yerix Ramadhani; Bastomi Baharsyah (Pusat Riset dan Inovasi Nasional, 2025)
Technology provides great opportunities for the plantation sector in increasing the efficiency and effectiveness of production management. PT. Adimulia Palmo Lestari (APL), as a company engaged in the oil palm plantation sector, faces challenges in the process of monitoring plantation results which are still carried out manually, so there is a risk of delays and inaccuracies in data. This study aims to design a website-based oil palm plantation monitoring service information system to facilitate the process of recording, reporting, and monitoring data in real time. The method used in designing this system is the waterfall method, which consists of the stages of needs analysis, system design, implementation, and testing. The results of this study are a web-based information system that is able to display harvest data in a structured manner, provide periodic reports, and facilitate access to information for management. The conclusion of this study shows that the implementation of a website-based information system can improve accuracy, efficiency, and transparency in the process of monitoring oil palm plantation results at PT. Adimulia Palmo Lestari (APL).